2021
DOI: 10.1097/icl.0000000000000814
|View full text |Cite|
|
Sign up to set email alerts
|

Relation Between Body Mass Index and Dry Eye Disease: The Japan Public Health Center–Based Prospective Study for the Next Generation

Abstract: Objective: To investigate the relation between body mass index (BMI) and dry eye disease (DED). Methods: We conducted a cross-sectional questionnaire-based survey in 85,264 Japanese men and women aged 40 to 74 years who participated in the Japan Public Health Center-based Prospective Study for the Next Generation (JPHC-NEXT Study). Dry eye disease was defined as the presence of severe symptoms or clinical diagnosis. A multivariable logistic regression model was used to estimate the odds ratios (ORs) of DED ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…33,34 An association between DED and body fat has been established. [35][36][37] As such, high BMI is a risk factor for DED and significantly affects tear film stability and the quality of tears. 35 Furthermore, an association between BMI and floppy eyelid syndrome has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 An association between DED and body fat has been established. [35][36][37] As such, high BMI is a risk factor for DED and significantly affects tear film stability and the quality of tears. 35 Furthermore, an association between BMI and floppy eyelid syndrome has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study conducted among 305 subjects using a short dry eye questionnaire suggested a medium correlation (r = 0.34, p = 0.003) between dry eye and body fat percentage [ 38 ]. However, a recent study conducted in a very large Japanese population (n = 85,264) that included males and females (40–74 years) suggested an inverse relationship between the prevalence of dry eye and a high BMI [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these respondents, participants who had a history of any type of cancer, myocardial infarction, angina pectoris, stroke, heart failure, diabetes mellitus or depression were excluded (n=20 477). We considered that participants who frequently or regularly visited a hospital because of such conditions had a greater chance of consultation with an ophthalmologist 19. Responders without information on happiness were also excluded (n=1180).…”
Section: Methodsmentioning
confidence: 99%
“…We considered that participants who frequently or regularly visited a hospital because of such conditions had a greater chance of consultation with an ophthalmologist. 19 Responders without information on happiness were also excluded (n=1180). Finally, 92 397 responders were included in this study figure 1 .…”
Section: Methodsmentioning
confidence: 99%